The International Encyclopedia of Media Studies 2012
DOI: 10.1002/9781444361506.wbiems116
|View full text |Cite
|
Sign up to set email alerts
|

Gender‐Role Socialization in the Twenty‐First Century

Abstract: Gender‐role socialization has been a critical element in the study of mass communication since the late 1960s. This chapter will review our knowledge of this topic looking specifically at gender‐role images on television, including broadcast programs and commercials, children's TV, and teen movies. The chapter focuses specifically on research conducted during the first decade of the twenty‐first century examining images related to age, race, and occupation. A critical and key finding is that women continue to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…Since decision making is affected by behavioral characteristics, it is quite likely that gender will be a factor that influences decision making in the context of genetic counseling. Women can have different considerations, values and concerns than men, and are also perceived differently than men in different cultures (Awwad et al 2008;Inglehart and Norris 2003;Loo and Thorpe 1998;Signorielli 2012). Gender has been found to influence ethical decision making (Beekun et al 2010;Curtis et al 2012;Jaffee and Hyde 2000;Rothbart et al 1986).…”
Section: Gender Influencesmentioning
confidence: 99%
“…Since decision making is affected by behavioral characteristics, it is quite likely that gender will be a factor that influences decision making in the context of genetic counseling. Women can have different considerations, values and concerns than men, and are also perceived differently than men in different cultures (Awwad et al 2008;Inglehart and Norris 2003;Loo and Thorpe 1998;Signorielli 2012). Gender has been found to influence ethical decision making (Beekun et al 2010;Curtis et al 2012;Jaffee and Hyde 2000;Rothbart et al 1986).…”
Section: Gender Influencesmentioning
confidence: 99%
“…Moreover, studying gender representation remains of the utmost importance because watching television still is the most time-consuming pastime (Collins 2011; Signorielli 2012). As a result, television is seen as one of the main institutions associated with disseminating stereotyped views of the world and its gender roles.…”
mentioning
confidence: 99%
“…As a result, television is seen as one of the main institutions associated with disseminating stereotyped views of the world and its gender roles. From the theoretical vantage point of cultivation theory as well as social learning theory, television is confirmed as one of the main agents of socialization (Bandura 1977; Gerbner 1979; Signorielli 2012). Research has shown that television viewing contributes to the maintenance as well as the learning (molding) of gender stereotyped perceptions among children, adolescents, and adults (Larson 2001; McGhee and Frueh 1980; Signorielli 1989; Welch et al 1979).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While the above scholarship in media centers mostly on animated film, TV shows are far more prevalent in the everyday lives of children and tend to have a greater influence (Signorielli 2013). Popular TV shows, both on Netflix and cable channels such as Nickelodeon, are often watched daily.…”
Section: Cohabitation: Birds Squirrels Girls and Boysmentioning
confidence: 99%